Empowering Madrasah Ibtidaiyah Teachers in Improving Islamic Character Based on Tauhid Education - Choirun Niswah; Robbul Izzatin (Jurusan PGMI FTIK IAIN Metro Lampung, 2021)
This community service-based research was carried out to enable teachers to improve tauhid (monotheism) education-based Islamic character in Madrasah Ibtidaiyah (MI) Ma'had Islamy 1 Ulu Laut Palembang. The study was conducted thorugh a community service using School Action Research model, consisting of planning, action, observation, and reflection. The results showed a significant increase in religious manifestation character from 432 to 689. The other characters such relationship with self, relationship with other students, relationship with environment, nationalism also witnessed a notable rise. The increase in teacher activity in increasing Islamic character at the school was shown from their participation in forum group discussion, from 50% to 78%. Likewise, their active engagement in Islamic character building activity experienced an important increase to 85.9%. It concludes that teachers have a very strategic role in improving the Islamic character based on effective tauhid education by creating a religious atmosphere, internalizing values, role model and habituation.